How Leadership And Organizational Culture Shape Organizational Agility In Indonesian SMEs?? - Zulfia Khalid; Madhakomala R; Dedi Purwana (IJHCM (International Journal of Human Capital Management), 2020)
A highly competitive market has increased the importance of organizational agility in attaining competitiveness through strengthening leadership and organizational culture. This study aims at examining the effect of entrepreneurial leadership on organizational agility mediated by organizational culture in Indonesian Small and Medium-sized Enterprises. There was a lack of evidence on which entrepreneurial leadership could significantly influence organizational agility through organizational culture. Using simple random sampling technique, a total of 200 employees from the centre of Industrial Village in East Jakarta, Indonesia was selected as the sample. Data were obtained through survey method and quantitatively analysed using Structural Equation Modelling with LISREL 8.8 software. The findings show that entrepreneurial leadership and organizational culture respectively have positive and significant direct effects on organizational agility. Entrepreneurial leadership has a positive and significant direct effect on organizational culture, and entrepreneurial leadership has a positive and significant indirect effect on organizational agility mediated by organizational culture. The research findings can provide guidelines for the SMEs entrepreneur to facilitate appropriate leadership and organizational culture, so as to foster organizational agility and achieve business benefits.